Application of nano-surface and molecular-orientation limited proteolysis to LC–MS bioanalysis of cetuximab. (May 2016) - Iwamoto, Noriko; Takanashi, Megumi; Umino, Yukari; Aoki, Chikage; Hamada, Akinobu; Shimada, Takashi
Background: We recently reported the principle of nano-surface and molecular-orientation limited (nSMOL) proteolysis, which is useful for LC–MS bioanalysis of antibody drugs.Methodology: The nSMOL is a Fab-selective limited proteolysis which utilizes the difference of protease-immobilized nanoparticle diameter (200 nm) and antibody collection resin pore (100 nm). We have demonstrated the full validation for chimeric antibody cetuximab bioanalysis in human plasma using nSMOL. Signature peptides (SQVFFK, ASQSIGTNIHWYQQR and YASESISGIPSR) in cetuximab complementarity-determining region were simultaneously quantitated by LC–MS multiple reaction monitoring.Conclusion: This nSMOL quantification showed sensitivity of 0.586 µg/ml and linearity of 0.586 to 300 µg/ml. Full validation study archived the guideline criteria of low Mw drug compounds. These results indicate that nSMOL is also significant method for cetuximab bioanalysis.